2020
DOI: 10.1080/13696998.2020.1721508
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential cost-effectiveness of a gene therapy for the treatment of hemophilia A

Abstract: Aim: Hemophilia A is a genetic, chronic disorder classified by deficient or defective coagulation factor VIII (FVIII) that puts those affected at risk for spontaneous bleeding episodes, which lead to joint damage and chronic pain over time. Currently, most severe hemophilia A patients are treated with prophylactic FVIII, which requires costly and frequent infusions and lifelong adherence to medication. A gene therapy (valoctocogene roxaparvovec) is currently in development for the treatment of severe hemophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…We have omitted the clinical costs of delivering gene therapy in our analysis, which are often higher than conventional therapeutics due to the need for inpatient hospital care. While there are cases where gene therapy is predicted to provide net cost-savings in treatment after accounting for the direct medical cost (e.g., valoctocogene roxaparvovec for the management of hemophilia A [80]), there is not yet evidence showing that gene therapy will result in net long-term cost savings. In addition, research has shown that new medical technologies generally raise health costs, and that cost-increasing changes in treatments outweigh cost-saving changes the majority of the time [102].…”
Section: Resultsmentioning
confidence: 99%
“…We have omitted the clinical costs of delivering gene therapy in our analysis, which are often higher than conventional therapeutics due to the need for inpatient hospital care. While there are cases where gene therapy is predicted to provide net cost-savings in treatment after accounting for the direct medical cost (e.g., valoctocogene roxaparvovec for the management of hemophilia A [80]), there is not yet evidence showing that gene therapy will result in net long-term cost savings. In addition, research has shown that new medical technologies generally raise health costs, and that cost-increasing changes in treatments outweigh cost-saving changes the majority of the time [102].…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory guidelines and requirements differ widely and are at different levels of development across countries, but often details are similar and aligned with regulations by the EMA or US FDA. The market price of vector may be high; however, detailed cost‐effectiveness analyses for prolonged or life‐time persistence of factor expression are needed for each country or region 82,83 . Such data will inform the development of adequate funding models and pricing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…24 Zhou et al and Cook et al estimated approximately $23 million for lifetime medical costs associated with prophylactic FVIII. 25,26 Machin et al projected 10-year medical costs of approximately $2 million for prophylactic FVIII. 27 Croteau et al calculated annual FVIII drug costs of more than $700,000, 23 although a more recent estimate by Croteau et al suggests a lower range of $400,000-$550,000, 28 depending on alternative indicators of annual prophylactic use.…”
Section: Commentarymentioning
confidence: 99%
“…5,6 Cook et al constructed a lifetime CEA model of valoctocogene roxaparvovec with an assumed upfront price of $2 million and total medical cost of $17 million. 26 Both studies-assuming a decline in endogenous FVIII following valoctocogene roxaparvovec treatment-projected that valoctocogene roxaparvovec would be cost saving when compared with prophylactic FVIII. 5,6,26…”
Section: Tablementioning
confidence: 99%